2022
DOI: 10.1155/2022/1150390
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of AT-Rich Interaction Domain (ARID) Family Members in Patients with Hepatocellular Carcinoma

Abstract: Objective. Hepatocellular carcinoma (HCC) is one of the most lethal malignancies with a poor prognosis. The AT-rich interaction domain (ARID) family plays an essential regulatory role in the pathogenesis and progression of cancers. This study aims to evaluate the prognostic value and clinical significance of human ARID family genes in HCC. Methods. ONCOMINE and The Cancer Genome Atlas (TCGA) databases were employed to retrieve ARIDs expression profile and clinicopathological information of HCC. Kaplan–Meier pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…BAF plays role in remodelling chromatin structure by removing or deleting nucleosomes to create the space for transcription factor binding, which is crucial for gene regulation [ 3 , 4 ]. ARID1A gene also serves as a tumor suppressor and is frequently mutated in several cancers, including bladder [ 5 ], hepatic [ 6 ], colorectal [ 7 ] and renal [ 8 ] cancers. Besides, the decreased ARID1A expression correlates with the poor outcome of cancers [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…BAF plays role in remodelling chromatin structure by removing or deleting nucleosomes to create the space for transcription factor binding, which is crucial for gene regulation [ 3 , 4 ]. ARID1A gene also serves as a tumor suppressor and is frequently mutated in several cancers, including bladder [ 5 ], hepatic [ 6 ], colorectal [ 7 ] and renal [ 8 ] cancers. Besides, the decreased ARID1A expression correlates with the poor outcome of cancers [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al described the function of KDM5D in the development of cisplatin [CDDP, abbreviation for cisdiamino-dichloroplatinum (II)] tolerance in head and neck squamous cell carcinoma (HNSCC) (32). Decreased KDM5D expression was also observed in gastric, colorectal, and hepatocellular carcinomas (33)(34)(35). Moreover, in an analysis of the TCGA database, Duan et al showed that KDM5D was signi cantly downregulated in 24 different cancer types (e.g., breast, pancreatic, or prostate cancer) compared with adjacent tissues (36).…”
Section: Introductionmentioning
confidence: 99%